Variations in Hypoxia Impairs Muscle Oxygenation and Performance during Simulated Team-Sport Running - Sweeting, Alice J.; Billaut, François; Varley, Matthew C.; Rodriguez, Ramón F.; Hopkins, William G.; Aughey, Robert J. (Frontiers in Physiology, 2017)
Purpose: To quantify the effect of acute hypoxia on muscle oxygenation and power during simulated team-sport running. Method: Seven individuals performed repeated and single sprint efforts, embedded in a simulated team-sport running protocol, on a non-motorized treadmill in normoxia (sea-level) and acute normobaric hypoxia (simulated altitudes of 2000 m and 3000 m). Mean and peak power was quantified during all sprints and repeated sprints. Mean total work, heart rate, blood oxygen saturation, and quadriceps muscle deoxyhaemoglobin concentration (assessed via near-infrared spectroscopy) were measured over the entire protocol. A linear mixed model was used to estimate performance and physiological effects across each half of the protocol. Changes were expressed in standardized units for assessment of magnitude. Uncertainty in the changes was expressed as a 90% confidence interval and interpreted via non-clinical magnitude-based inference. Results: Mean total work was reduced at 2000 m (-10%, 90% confidence limits ±6%) and 3000 m (-15%, ±5%) compared with sea-level. Mean heart rate was reduced at 3000 m compared with 2000 m (-3, ±3 min-1) and sea-level (-3, ±3 min-1). Blood oxygen saturation was lower at 2000 m (-8, ±3 %) and 3000 m (-15, ±2 %) compared with sea-level. Sprint mean power across the entire protocol was reduced at 3000 m compared with 2000 m (-12%, ±3%) and sea-level (-14%, ±4%). In the second half of the protocol, sprint mean power was reduced at 3000 m compared to 2000 m (-6%, ±4%). Sprint mean peak power across the entire protocol was lowered at 2000 m (-10%, ±6%) and 3000 m (-16%, ±6%) compared with sea-level. During repeated sprints, mean peak power was lower at 2000 m (-8%, ±7%) and 3000 m (-8%, ±7%) compared with sea-level. In the second half of the protocol, repeated sprint mean power was reduced at 3000 m compared to 2000 m (-7%, ±5%) and sea-level (-9%, ±5%). Quadriceps muscle deoxyhaemoglobin concentration was lowered at 3000 m compared to 2000 m (-10, ±12 %) and sea-level (-11, ±12 %). Conclusions: Simulated team-sport running is impaired at 3000 m compared to 2000 m and sea-level, likely due to a higher muscle deoxygenation.